SECURITY ENGINEERING USING DATA ONLINE TRANSACTIONS ON cryptography - Rahayu Noveandini (JAKSTIK Journal, 2006)
E-commerce is a means to conduct financial transactions online. Facility has grown rapidly since the beginning of its use in 1970. When is e-commerce is only about the commercial documents like purchase orders or invoices electronically. Now e-commerce has included credit card transactions, enterprise resource planning, and others. One method of securing the network is the use of technology, Secure Socket Layer (SSL). This technology allows the client to build a secure and encrypted connection with the server. In addition there is also a Digital Certificate technology allows a client to know whether the site's pages are accessible genuine or fake. Both technologies are then put together to facilitate e-commerce to be safe and prevent users from feeling anxious. There are several things that must be prepared to secure e-commerce. From the server side is the availability SSL technology, Digital Certificate, encrypting data, and so forth. To be able to use this technology, there are certain steps that must be taken lankah. While the readiness of the client side of client / server capabilities to rival browsers such as browser capabilities in running SSL.   Many of the lurking threat of e-commerce users. One is phishing. These crimes take advantage of the use of fake websites to deceive users of e-commerce so that when the user accesses such sites important information can be stolen from him by the offender. This crime other than relying on technology also relies on a user's attention ketidakhati in accessing e- commerce site.   Actually, the safety factor of e-commerce does not only depend on the sophistication of the technology used, but more emphasis on prudence and accuracy of e-commerce users in keeping the information themselves, and notice what he had access to the internet. Technology that determines it is safe or not was not only the technology that is used, but also the readiness of human resources in use.